Representation of Photisms in the English Translations of V. Nabokov’s Novels “The Gift” and “Laughter in the Dark” - Liudmila V. Krivoshlykova; Leonid V. Lebedev (RUDN Journal of Language Studies, Semiotics and Semantics)
The study of the phenomenon of synesthesia in the discourse of artistic texts are relevant today. The novels “The Gift” and “Camera Obscura” by the synesthetic author V. Nabokov, as well as their translations into English, serve as the objects of research. The study of the phenomenon of synesthesia and its manifestations in artistic texts will allow describe the structure of the authorsynesthete Vladimir Nabokov’s figurative perception and identify the structural linguistic and translational features of his works. The materials for the study were the texts of the novels “The Gift” and “Camera Obscura” in Russian and English. The results of the study consist of describing and structuring the influence of the author’s synesthetic perception on the structural organization of the literary text, as well as on the formation of literary characters. In addition, the use of synesthetic images significantly complicates the work of translating literary texts due to the peculiarities of the author’s complex perception of images.